Incidence and clinical outcomes of bleeding complications and acute limb ischemia in STEMI and cardiogenic shock. Issue 6 (30th May 2020) - Pahuja, Mohit; Ranka, Sagar; Chehab, Omar; Mishra, Tushar; Akintoye, Emmanuel; Adegbala, Oluwole; Yassin, Ahmed S.; Ando, Tomo; Thayer, Katherine L.; Shah, Palak; Kimmelstiel, Carey D.; Salehi, Payam; et al.
Abstract: Background: Bleeding complications and acute limb ischemia (ALI) are devastating vascular complications in patients with ST‐segment elevation myocardial infarction (STEMI). Cardiogenic shock (CS) can further increase this risk due to multiorgan failure. In the contemporary era, percutaneous mechanical circulatory support is commonly used for management of CS. We hypothesized that vascular complications may be an important determinant of clinical outcomes for CS due to STEMI (CS‐STEMI). Objective: We evaluated 10‐year national trends, resource utilization and outcomes of bleeding complications, and ALI in CS‐STEMI. Methods: We performed a retrospective cohort study of CS‐STEMI patients from a large U.S. national database (National Inpatient Sample) between 2005 and 2014. Events were then divided into four different groups: no MCS, with intra‐aortic balloon pump, percutaneous ventricular assist device includes Impella or Tandem Heart or extracorporeal membrane oxygenation. Results: Bleeding complications and ALI were observed in 31, 389 (18.2%) and 1, 628 (0.9%) out of 172, 491 admissions with CS‐STEMI, respectively. Between 2005 and 2014, overall trends increased for ALI; however, the number of bleeding events decreased. ALI was associated with increased in‐hospital mortality in comparison to those without any ALI. However, bleeding complications were not associated with increased in‐hospital mortality. Compared to patients without complications, both bleeding and ALI were associated with increased length of stay (LOS) and hospitalization costs. Conclusions: Bleeding and ALI are common complications associated with CS‐STEMI in the contemporary era. Both complications are associated with increased hospital costs and LOS. These findings highlight the need to develop algorithms focused on vascular safety in CS‐STEMI.